Changes of size and structure of world population of European bison in years 2000–2015 (European Bison Conservation Newsletter, 2016)
Analysed were data on the number of individuals, a number of herds, and proportion of both genetic lines for the end of years 2000, 2005, 2010 and 2015, to verify the implementation of recommendations provided by the Action Plan on 2004. Observed was a dynamic increment of both: numbers of wisent herds (from 221 to 296), and population numbers (from 2793 to 6083). The proportion of individuals in captivity in relation to free ranging and semi free parts of the population dropped from over 41% in 2000 to only 27.5% in 2015. The percentage of wisents belonging to Lowland line in captivity grew up from 25.6 to 32.7% since the year 2000, and in free ranging and semi free herds, individuals belonging to the Lowland line constituted 56.6% in 2000, while now they exceed 61.5% of this part of world population. In that period, decreased by almost 6% the proportion of wisent groups counting 20 individuals.
Keywords: wisent; world population; population dynamics; population structure; captivity; free ranging